Attitudes, Behavior and Relations in the Early School Years - Geert Driessen (MDPI AG, 2022)
In the early school years, the emphasis is more and more on cognitive output factors. Non-cognitive development is receiving less attention than before, though such factors are important determinants of academic success. This study aims at answering two questions: (1) How do young children perform on a number of non-cognitive characteristics, more specifically, attitudes, behavior, and relationships? (2) Are there any differences with regard to those characteristics according to the pupils' social and ethnic/immigrant background? To answer the questions, data from the Dutch large-scale cohort study COOL5-18 were analyzed. The main sample included nearly 6500 grade 2 pupils (6-year-olds). Teachers answered questions about their pupils' attitudes, behavior, and relationships. One- and two-way analyses of variance were employed, and effect sizes were computed. The results showed that the teachers rated their pupil's work attitude as lower than their behavior and popularity. They were more positive regarding their relationship with the pupils. More important was that there were differences according to the pupils' social and ethnic/immigrant backgrounds: ethnic minority/immigrant pupils scored less positive on all non-cognitive characteristics than native Dutch pupils, and the higher the parental educational level, the more favorable their children performed on the non-cognitive characteristics. These findings are discussed and possible solutions are presented.